(untitled) (Revista Espiga, 2023)
The objective of this article is to provide a critical understanding of the legal and conceptual challenges in combating human trafficking for sexual exploitation. This type of trafficking affects vulnerable individuals and expands due to illegal migration and migration restrictions. The article critically analyzes the conceptualization of the victim within the international legal framework and the various schools of thought that address this differentiation. The origins of this issue and some of its legal consequences are explored in Colombia and Mexico, countries considered as source countries in the migratory context. While states have made efforts to combat this crime through international conventions, there is still disagreement regarding the number of individuals directly affected, due to problems in defining trafficking victims and their inadequate relationship with sex work.